Psychological Impact of Early Childhood Development Due to Sexual Violence (Universitas Negeri Semarang, 2021)
In this day and age there are many problems with children. how not at a very early age and need good development and in the content of things that are posistif actually damaged. The rights of the child are usurped by irresponsible people. For example, such as sexual violence that can cause child development so unclear. Sexual violence itself is increasing significantly and the rate of sexual violence in Indonesian children almost every year rises. This is due to lack of attention and less serious attention. So that the most common negative effect felt by the victim is psychological damage. So that the occurrence of psychological damage can cause negative effects of long-term for children.